Etika Sosial dalam Imamat 19:18 sebagai Landasan Praksis Sila Kedua Pancasila - Hagai Zefanya Putra; Merry Kristina Rungkat (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. This article discusses how the principle of social ethics in Leviticus 19:18 can relate to the humanitarian values contained in the second principle of Pancasila, namely